1995
DOI: 10.1021/jo00109a050
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Structure of Caribenolide I, a Highly Potent Antitumor Macrolide from a Cultured Free-Swimming Caribbean Dinoflagellate, Amphidinium sp. S1-36-5

Abstract: H31a, 70H, H8a, H8b OH: 3.69 br d 6.2 (H7) 8 45.0 a: 2.93 dd 10.1 (H7), 16.7 (H8b) b: 2.64 dd 2.4 (H7), 16.7 (H8a) 9 211.3 10 47.7 3.36 dq 9.9 (HU), 6.6 (H32) 11 126.4 5.02 br d 10.1 (H10), (13a, 33) 12 136.4 13 39.8 a: 2.38 br d 13.3 (H13b), H14, H33, 140H b: 2.17 dd 13.3 (H13a), 11.4 (H14), H33 14 70.4 4.06 br dd 11.4, 2.9 (H13a, 13b)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0
2

Year Published

2000
2000
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(51 citation statements)
references
References 1 publication
1
48
0
2
Order By: Relevance
“…Although the relative configurations at C-14, C-15, C-16, and C-19 were indicated as shown, the other relative stereochemistry as well as the absolute stereochemistry of 13 have not been determined. Shimizu and co-workers isolated an amphidinolide N-type macrorolide, named caribenolide I [35], from a free-swimming dinoflagellate Amphidinium operculatum ver nov Gibbosum, which showed antitumor activity against murine leukemia P388 in vivo.…”
Section: -4 Amphidinolide Nmentioning
confidence: 99%
“…Although the relative configurations at C-14, C-15, C-16, and C-19 were indicated as shown, the other relative stereochemistry as well as the absolute stereochemistry of 13 have not been determined. Shimizu and co-workers isolated an amphidinolide N-type macrorolide, named caribenolide I [35], from a free-swimming dinoflagellate Amphidinium operculatum ver nov Gibbosum, which showed antitumor activity against murine leukemia P388 in vivo.…”
Section: -4 Amphidinolide Nmentioning
confidence: 99%
“…P388. Of even greater potency was the macrolide caribenolide (8) (Bauer et al, 1996;, which showed a mean IC 50 of 1.6 nM and, likewise, had limited cell line selectivity. Using limited supplies, activity against ip/ip P388 was established (50% lifespan increase), but no distal site antitumor activity could be shown against i.v.…”
Section: Mass Scale Cultivation and Isolation Of Metabolitesmentioning
confidence: 99%
“…In the last decade, some species belonging to this group have gained attention and are being used as a 'model' organism for research into dinoflagellate genetics, polyketide production (including cytotoxins and ichthyotoxins), and photosynthesis (Kobayashi et al 1991;Satake et al 1991;Bauer et al 1994Bauer et al , 1995Paul et al 1996;Houdai et al 2001;Damjanovic et al 2000;Kleima-Foske et al 2000a, b, Ten Lohuis andMiller 1998;Kubota et al 2006). Even though Amphidinium forms a dominant phytobenthos and known to be a nice prey for protistan grazers (Jeong et al 2001), its ecological significance in their role as primary producer, biogeochemical cycling, and food-web dynamics in the benthic system is largely unknown.…”
Section: Identification and Distribution Of Amphidiniummentioning
confidence: 99%